Examining the functional movement screen and y balance test scores in a cohort of intercollegiate athletes before and after a training intervention - Liljeberg, J. E. (University of Delaware, 2018)
The number of lower extremity (LE) injuries in Division-I collegiate student-athletes has consistently increased over the past 10 years. Given these steady trends, a reliable screening tool is essential to predict an athlete`s risk of injury in order to enhance the safety and performance of this population. Even though research surrounding the FMS and YBT have been mixed, very few studies have looked at the effect of these test scores over time and its effect on strength. The primary purpose of this study was to compare both YBT and FMS scores in NCAA Division-I student-athletes before and after a supervised strength and conditioning-based intervention. This prospective cohort study had 122 participants (42 males, 80 females) (age=19.6 ± 1.1, height 174.3 ± 8.2, mass 70.4 ± 9.4). Each participant completed the FMS, YBT, squat max, and bench press max testing at three separate time periods over a 17-month span. Of the total number of participants, those that obtained a LE injury were classified as LE injured (n=50) and those that were not, were classified as healthy (n=72). A one-way analysis of variance was used to compare scores between the two screening tools; a Tukey post-hoc was used to determine where significant differences took place across time. A two-group growth curve was used for the study`s second aim and third aim to determine if there was a difference between YBT and FMS scores of athletes who have or have not sustained LE injuries, as well as to compare maximum squat and bench press test results in studentathletes before, during, and after a strength and conditioning-based intervention. The following variables showed a significant difference over time: anterior difference (ANT Diff) (p<0.004), posteromedial difference (PM Diff) (p<0.011), PL Diff (p<0.035), YBT composite score difference (YBT COMP Diff) (p<0.001), deep squat (p<0.025), in-line lunge (p<0.001), max bench press (p<0.001), max squat (p<0.001), and LE injury (p<0.001). The following variables had a significant effect on maximum squat: ANT Diff (p=0.044, t=2.022), Deep Squat (p=0.029, t=2.189), Hurdle Step-Over (p=0.017, t=2.401), In-Line Lunge (p=0.006, t=2.759), and FMS COMP (p<0.001, t=5.108). Both PM Diff (p=0.02, t=2.332) and Deep Squat (p=0.002, t= -3.094) had a significant effect on LE injury. While previous research has not been in support of the FMS as an injury predictor, we believe that certain components, specifically the deep squat, may improve over time through a strength and conditioning program. Athletic trainers and strength and conditioning coaches should consider using the YBT as a pre-participation screening tool and symmetry measure between limbs. We believe that when utilizing the FMS and YBT, strength gains over time may influence these test scores.